Expression Pattern of a Homeotic Gene, HOXA5, in Normal Breast and in Breast Tumors - Gregory S. Henderson; Paul J. van Diest; Horst Burger; Jose Russo; Venu Raman (Cellular Oncology)
Introduction: Homeotic (HOX) gene products are now known to be functionally associated with breast cancer biogenesis. Recent evidence has indicated that HOXA5 regulates both p53 and progesterone receptor expression levels in breast cancer cells. In addition, HOXA5 has been shown to interact and regulate the activity of another protein referred to as Twist. As homeotic genes play a pivotal role in development, we sought to decipher the expression pattern in both normal breast tissues and in breast carcinomas. Methods: RT-PCR and immunohistochemistry were performed, to assay the levels of HOXA5 expression, on a panel of normal breast tissue and its corresponding primary breast tumors. Results and Conclusions: We show that HOXA5 expression was maintained at stable levels at different reproductive stages of a woman's life, except during lactation. This evidence indicates that HOXA5 may play a role in maintaining the differentiated state within the breast epithelium. However, nearly 70% of all breast carcinomas had decreased HOXA5 protein levels as compared to normal breast tissues. In addition, we demonstrate that HOXA5 protein expression levels in breast carcinomas inversely co-relates with Epidermal Growth Factor Receptor (EGFR) expression. Furthermore, we found that the survival rate amongst the different low levels of HOXA5 expressing breast tumors was not significant, indicative of an early tumorigenesis process in the absence of innate levels of HOXA5 in normal breast cells.